Preprečevanje prenosa ESBL-pozitivnih bakterij v domu starejših občanov in ozaveščenost negovalnega osebja - Fijan, Sabina (Obzornik zdravstvene nege, 2013)
Introduction: ESBL-producing bacteria are resistant to many different antibiotics that are used in the treatment of infections and are mainly spread among people in hospitals and long-term care facilities. The most important ways to prevent transmission of ESBLproducing bacteria is washing and disinfecting hands of the nursing staff, the use of protective gloves, cleaning and disinfecting the surfaces and appliances for nursing care. Methods: The aim of the study performed in one of the old people's home was to determine the nurses' knowledge of ESBL-producing bacteria as well as the general and special precautions regarding the prevention of the spread of these organisms. The data were acquired through a structured questionnaire including questions about hand washing and disinfection as primary prevention method. Results: Results of the study show that 75 % of the nursing personnel are familiar with the ESBL-producing bacteria and 96.6 % of the respondents reported that the most common mode of transmission of ESBL-producing bacteria is a transmission by direct contact. The majority of the respondents were familiar with the protective measures against infections caused by ESBL-producing bacteria. Discussion and conclusion: While not all infections in old people's homes can be prevented, the vast majority of them can be reduced to the lowest acceptable level by educating the staff, adherence to guidelines for infection control and rigorous implementation of infection prevention procedures, especially washing and disinfecting hands and appliances.
Keywords: bolnišnične okužbe; elderly; Extended spectrum beta-lactamase; hand disinfection; hospital-acquired infections; nursing home; razkuževanje rok; starostniki